The Epigenetic Modification of SLC5A8 in Papillary Thyroid Carcinoma and Its Effects on Clinic-Pathological Features - Sara Sheikkholeslami; Fereidoun Azizi; Asghar Ghasemi; Abbas Alibakhshi; Hossein Parsa; Setareh Shivaee; Marjan Zarif-Yeganeh; Mehdi Hedayati; Ladan Teimoori-Toolabi (Tehran University of Medical Sciences, 2022)
Background: Epigenetic alterations such as DNA methylation are known as the main cause of different types of cancers through inactivation of tumor suppressor genes, especially thyroid cancer. Identification of novel and effective markers are important in diagnosis and prevention of thyroid cancer. In the present study, the expression and methylation of Solute carrier family 5 member 8 (SLC5A8) in Papillary Thyroid Carcinoma (PTC) in comparison to multinodular goiter (MNG) have been studied. Methods: Overall, 41 patients with PTC and 36 patients affected by MNG were recruited from four hospitals in Tehran and Qazvin, Iran in 2018. Thyroid tissues were obtained during thyroidectomy. RNA and DNA were extracted from thyroid tissues. Quantitative RT-PCR assay was performed for determining the mRNA level of SLC5A8 while Methylation-Sensitive High-Resolution Methylation was applied for assessing the methylation status. Results: Methylation status of three regions composed of 52 CpG islands in the promoter of SLC5A8 gene was studied by HRM assay. SLC5A8 level in PTC tissues was significantly downregulated in average 0.4 fold in comparison with MNG tissues (P=0.05). The aberrant methylation of SLC5A8 (b) region was remarkably different in PTC and MNG cases. The promoter methylation of SLC5A8 (c) was significantly related to BRAF mutations and vascular invasion in PTC patients. Conclusion: The aberrant promoter hyper methylation of SLC5A8 was related to aggressive PTC. Therefore, there is some evidence to support the hypothesis that SLC5A8 could be a paly important role in the development of PTC.